2020
DOI: 10.3390/ma13081998
|View full text |Cite
|
Sign up to set email alerts
|

Biphenyl Wrinkled Mesoporous Silica Nanoparticles for pH-Responsive Doxorubicin Drug Delivery

Abstract: Biphenyl wrinkled mesoporous silica nanoparticles with controlled particle size and high surface area were evaluated for the storage and delivery of doxorubicin. The average particle size and surface area were ~70 nm and ~1100 m2/g. The doxorubicin loading efficiency was 38.2 ± 1.5 (w/w)% and the release was pH dependent. The breast cancer cell line, MCF-7 (Michigan Cancer Foundation-7) was used for the in vitro drug release study. The cytotoxicity of doxorubicin-loaded nanoparticles was significantly higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Our research team is among the first to study KCC-1 for DDSs [42,43,68,69], and we think that research on KCC-1 will increase soon. In the literature, there are references to "spherical wrinkled mesoporous silica" (WMS) [70][71][72] and KCC-1 is known also "dendritic fibrous nano-silica" (DFNS) [73]. They were all obtained based on changing the synthesis conditions and parameters of the original synthesis method for KCC-1 particles.…”
Section: Discovery Synthesis and Properties Of Msnsmentioning
confidence: 99%
“…Our research team is among the first to study KCC-1 for DDSs [42,43,68,69], and we think that research on KCC-1 will increase soon. In the literature, there are references to "spherical wrinkled mesoporous silica" (WMS) [70][71][72] and KCC-1 is known also "dendritic fibrous nano-silica" (DFNS) [73]. They were all obtained based on changing the synthesis conditions and parameters of the original synthesis method for KCC-1 particles.…”
Section: Discovery Synthesis and Properties Of Msnsmentioning
confidence: 99%
“…In contrast, cells internalize nanoparticles, which involves a binding (adsorbing) process followed by the formation of vesicles, and then, the formed nanoparticle-containing vesicles are internalized by endocytosis [ 11 ]. It has been reported that a nanoparticle size of ~50 nm may result in higher tumor cell uptake and mesoporous silica nanoparticles ~50 nm in diameter had the highest loading in HeLa cells [ 57 , 58 ]. In our study, ~50 nm QD-SFNPs (~170 nm in wet state) showed the possibility of being internalized by EA.hy926 and HeLa cells ( Figure 9 , seen in the circle symbols).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, chemotherapy drugs used for breast cancer include anthracyclines such as doxorubicin (DOX), 5,6 taxanes such as paclitaxel, 5,7 5‐fluorouracil (5‐FU), 8 cyclophosphamide (neosar, cytoxan), and carboplatin (paraplatin) 9 . In this regard, DOX is one of the most common drugs that possess low bioavailability due to poor solubility in water (the hydrophobic version of doxorubicin [doxorubicin free base]) 10–12 . Generally, DOX possesses cell‐cycle‐specific activities and not only leads to G0/S and G2/M arrest but also results in apoptosis due to the increases of oxygen radicals 13 .…”
Section: Introductionmentioning
confidence: 99%